Deyanira y Heracles en Sófocles. La esposa y el héroe: dos mundos opuestos - López Férez, Juan Antonio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
Sophocles offers a simple plot in his Trachiniae: a lonely wife (Deianeira) lives at home, fearful of any evil which could occur to her husband. He very often is out of his house and has frequent sexual intercourses with other women. Heracles, always respectful with gods, does not care about his family: wife, children, home. As final proof of his insolence and brutality he sends his lover (Iole) to his home, without any explanations. Deianeira, always pacient till then, decides to conquer her husband with a love potion, which will really be a letal poison. Deianeira kills herself in a rather virile manner, running herself through with a sword. Heracles, seriously ill, cries like a woman, asks for help and piety, unable of anything, and adquires some rather feminine ways. Exam of conspicuous passages of the piece, underlining the opposition of two worlds: the pacient wife in front of a brutal and thoughtless hero.